Qualitative study on the ability of neurological nurses to manage patients with indwelling gastrointestinal canal - Wang, Zezhou; Liu, Yan; Fang, Kui; Hao, Xixi; Xue, Zhihan; Dong, Xue; Wang, Haijun (Frontiers in Medicine, 2024)
Aim and objectives This study aims to assess the proficiency of nurses in the neurology department in managing patients with indwelling gastrointestinal canal. Background Many critically ill patients in neurology departments require the placement of nasoenteric tubes to provide enteral nutrition. However, in clinical practice, there exists considerable variability in nurses’ competencies regarding the management of patients with nasoenteric tubes. A thorough understanding of the challenges nurses face throughout the entire process of nasoenteric tube care and the development of targeted improvement measures are crucial for delivering enhanced patient care and facilitating patient recovery. Design A qualitative interview study. Methods From August to October 2023, 11 neurological nurses were recruited offline in three hospitals for semi-structured and in-depth interviews. The data analysis uses the KJ method to summarize and classify the themes from the semi-structured interview results, and then organize the themes into a coherent visual and logical path. The COREQ list is used. Results The researchers conducted semi-structured interviews with 11 neurology nurses from three hospitals using a purposive sampling method, of which 64% of the participants were female and 36% were male; the average age was 38.27 ± 7.85 years; 27% from the Department of Neurology, 73% from the Department of Neurosurgery; junior professional titles accounted for 18%, intermediate professional titles accounted for 64%, senior professional titles accounted for 18%; 27% of the subjects were head nurses and 73% were nurses. The study identified 5 themes: (1) Preparation and evaluation before intubation; (2) Enhancement of intubation success rates; (3) Prevention of complications; (4) Management of complications and emergencies; (5) The acquisition of relevant knowledge and experience. In clinical practice, the bedside blind insertion technique is random and has not yet formed a unified standard, and the specific operation details and techniques need to be further improved. Conclusion Disparities exist in the nursing capabilities of neurology nurses due to variations in their knowledge and experience regarding gastrointestinal canal management.